Wider, deeper, higher - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
This is the age of the network, where any person on earth can reach any other person by passing through no more than three intermediaries, and without even using mass media. This simple sum and its simplicity does not always work, not least in...